Anti-TIF1-γ antibody and cancer-associated myositis: A clinicohistopathologic study. (19th July 2016) - Hida, Ayumi; Yamashita, Takenari; Hosono, Yuji; Inoue, Manami; Kaida, Kenichi; Kadoya, Masato; Miwa, Yusuke; Yajima, Nobuyuki; Maezawa, Reika; Arai, Satoko; Kurasawa, Kazuhiro; Ito, Kazuhiro; et al.
Abstract : Objective: We aimed to analyze the clinical and histopathologic features of cancer-associated myositis (CAM) in relation to anti–transcriptional intermediary factor 1 γ antibody (anti-TIF1-γ-Ab), a marker of cancer association. Methods: We retrospectively studied 349 patients with idiopathic inflammatory myopathies (IIMs), including 284 patients with pretreatment biopsy samples available. For the classification of IIMs, the European Neuromuscular Center criteria were applied. Patients with CAM with (anti-TIF1-γ-Ab[+] CAM) and without anti-TIF1-γ-Ab (anti-TIF1-γ-Ab[−] CAM) were compared with patients with IIM without cancers within and beyond 3 years of myositis diagnosis. Results: Cancer was detected in 75 patients, of whom 36 (48%) were positive for anti-TIF1-γ-Ab. In anti-TIF1-γ-Ab(+) patients with CAM, cancers were detected within 1 year of myositis diagnosis in 35 (97%) and before 1 year of myositis diagnosis in 1. All the anti-TIF1-γ-Ab(+) patients with CAM satisfied the dermatomyositis (DM) criteria, including 2 possible DM sine dermatitis cases, and were characterized histologically by the presence of perifascicular atrophy, vacuolated fibers (VFs), and dense C5b-9 deposits on capillaries (dC5b-9). In contrast, 39 anti-TIF1-γ-Ab(−) patients with CAM were classified into various subgroups, and characterized by a higher frequency of necrotizing autoimmune myopathy (NAM). Notably, all 7 patients with CAM classified into the NAM subgroup were anti-TIF1-γ-Ab(−) and exhibited no dC5b-9 or VFs. Conclusions: CAM includes clinicohistopathologically heterogeneous disease entities. Among CAM entities, anti-TIF1-γ-Ab(+) CAM has characteristically shown a close temporal association with cancer detection and the histopathologic findings of dC5b-9 and VFs, and CAM with NAM is a subset of anti-TIF1-γ-Ab(−) CAM.